(untitled) (PerCursos, 2021)
The present paper seeks to demonstrate the thesis of the temporal milestone as a deconstruction of the new paradigm regarding indigenous peoples present in the 1988 Federal Constitution. Until the 1988 Constitution, the indigenous peoples’ right to be on their lands was, in some way, recognized but not the right to remain indigenous, therefore, integration was seen as necessary. In 1988, this paradigm changed and integration was not included in the law. The rights to be and remain as indigenous peoples are recognized, in addition to the primary law to the lands they occupy recognition. This recognition happened mainly due to the struggle of the indigenous peoples that have resisted for 520 years. However, the Supreme Federal Court created the thesis of the temporal milestone that implies that indigenous people are only entitled to their territory if they were there on October 5th 1988. Thereby, the country’s largest court disregards indigenous peoples’ struggle and the violence that expelled them from their lands so many times. Therefore, the main objective is to critically analyze the thesis of the temporal milestone and demonstrate that it is contrary to the constitution itself and disregards the struggle and resistance of the indigenous peoples. For this, a historical analysis of the indigenous peoples’ rights is made, the case is presented highlighting the votes of the Ministers and then, we presented arguments that demonstrate that the thesis of the temporal milestone means, to a certain extent, the return of the integration ideal and the mitigation of the indigenous peoples’ rights.